Preliminary Evaluation of Educational Outreach to Promote Colorectal Cancer Screening Among South Asians in the San Francisco Bay Area - Mukherjea, Arnab; Ansari, Zahra K.; Senthil Kumar, Sailakshmi; Katyal, Toshali; Sahota, Dilpreet S.; Handa, Raja; Ivey, Susan L. (Journal of immigrant and minority health, 2020)
Culturally-tailored interventions increase rates of colorectal cancer (CRC) screening in diverse populations. South Asian Americans have very low rates of CRC screening. Targeted interventions may improve community awareness and likelihood of undergoing screening. We identified and recruited multiple South Asian-serving community and religious centers to conduct South Asian physician-led presentations about CRC screening. A post-presentation survey tool was used to evaluate CRC screening history, intent to screen, and acceptance of a tailored brochure. In a convenience sample of 103 surveys, many participants had not undergone screening in the past (48%), and intent to screen after the presentation was high in those previously not screened (87%). Those who took a culturally-tailored brochure said they would share materials with family and friends (95% and 39% respectively). Our results support earlier findings of success in culturally-tailored interventions and indicate acceptance of culturally-tailored CRC screening outreach in community sites.